Defining love: a philosophical, scientific, and theological engagement - Oord, Thomas Jay (Brazos Press, 2010)
Love and the science-and-theology symbiosis -- Love's diverse forms and multiple recipients -- Love and the social sciences -- Love and the biological sciences -- Love and cosmology -- A theology of love informed by the sciences